2020
DOI: 10.1016/j.enconman.2020.112698
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated functionalization of carbon derived corncob residue via hydrothermal synthesis route for esterification of palm fatty acid distillate

Abstract: Low-cost biodiesel was successfully produced through esterification of palm fatty acid distillate over corncob residue-derived heterogeneous solid acid catalyst. The sulfonated functionalized carbon derived from corncob was synthesized via hydrothermal carbonization followed by chemical activation using concentrated sulfuric acid. This technique allows efficient carbonization process and able to maintain active polar species of the catalyst hence effectively improves the acid strength of prepared catalyst. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 57 publications
1
27
1
3
Order By: Relevance
“…These drawbacks have gained significant attention in the search for different heterogeneous catalyst technologies for biodiesel synthesis. Recently, several studies stated solid basic or acidic heterogeneous catalysts for biodiesel production including, solid ferric hydrogen sulphate [Fe(HSO 4 ) 3 ] 10 , KF and NaNO 3 catalysts 11 , Calcined dolomite 12 , Calcium lanthanum mixed oxide 13 , Bi 2 O 3 –La 2 O 3 14 , calcium methoxide 15 , g-Al 2 O 3 /KI 16 , metal-doped methoxide 17 , sucrose-derived solid acid 18 , natural CaO 19 , sulfonated functionalized carbon 20 , ZrO 2 21 , Methoxy-functionalized mesostructured stable carbon 22 , sand dollar 8 . The application of these heterogeneous catalysts for biodiesel production overwhelms the homogeneous catalysts drawbacks due to their feasibility, easily recovered processes, tolerance to feedstock moisture and free fatty acid contents and reusability 13 .…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks have gained significant attention in the search for different heterogeneous catalyst technologies for biodiesel synthesis. Recently, several studies stated solid basic or acidic heterogeneous catalysts for biodiesel production including, solid ferric hydrogen sulphate [Fe(HSO 4 ) 3 ] 10 , KF and NaNO 3 catalysts 11 , Calcined dolomite 12 , Calcium lanthanum mixed oxide 13 , Bi 2 O 3 –La 2 O 3 14 , calcium methoxide 15 , g-Al 2 O 3 /KI 16 , metal-doped methoxide 17 , sucrose-derived solid acid 18 , natural CaO 19 , sulfonated functionalized carbon 20 , ZrO 2 21 , Methoxy-functionalized mesostructured stable carbon 22 , sand dollar 8 . The application of these heterogeneous catalysts for biodiesel production overwhelms the homogeneous catalysts drawbacks due to their feasibility, easily recovered processes, tolerance to feedstock moisture and free fatty acid contents and reusability 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst deactivation can be suppressed by employing catalyst regeneration and reactivation steps. 45 Although the sulfur was leached out into the biodiesel, the concentration detected was lower than the maximum limit (25 ppm) in ASTM D6751-02. 46 Overall, these ndings suggested that the reduction of the esterication activity in the spent sulfonated SnO 2 -spc catalyst aer four consecutive runs was due to the accumulation of carbon species, loss of acidic sites and leaching of S species.…”
Section: Reusability and Leaching Analysis Of The Sulfonated Sno 2spcmentioning
confidence: 86%
“…Such nanorods are strong and are made from iron, cobalt, and stable spinel ferrite materials. Since of the weak driving fields 21 the materials are adopted. Magnetic characteristics include chemical stability, biocompatibility and superparamagnetic characteristics.…”
Section: Magnetic Nanorodsmentioning
confidence: 99%
“…Its optimization has been observed to be dependent on its adsorbing capability. The adsorbing capability of the material in use is dependent on the pH, sonication time, adsorbent mass as well as other factors which should be considered 21 .…”
Section: Optimization Of Nanorods Materials Productionmentioning
confidence: 99%